Collective action to defend the rights of consumers and users - Benavides-Burbano, Lilia Fernanda; Murcia-González, Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This document aims to study the recognition of the rights of consumers in countries like Spain and Colombia. In the first case, the Spanish Constitution of 1978, Article 51, commits to the public powers the protection and strengthening of those rights. In Colombia the Constitution of 1991, article 78, makes an explicit recognition of the rights of the consumer. As a second step in this process are studied and analyzed legislative developments on the issue in the two countries. It must be emphasized that the guidelines that govern the system of protection of these rights can be guided to Spain and Colombia on this foundation: safety and quality of products, protection of economic and social interests, correct and sufficient information, education and training, representation, consultation and participation, and protection in situations of inferiority. Highlighted general  characteristics of protection to users, aspects of the protection mechanisms that give effect to the right in question are described, through a comparative analysis between the two laws.